Efficacy of Cognitive Behavioural Therapy on Mental Health Disorders among In-School Adolescents in Taraba State, Nigeria - Emmanuel, Atsue Terhile (Indonesian Journal of Educational Studies, 2025)
This study investigated the efficacy of Cognitive Behavioural Therapy (CBT) on mental health disorders among in-school adolescents in Taraba State, Nigeria. The study adopted a quasi-experimental research design, guided by two research questions and two null hypotheses tested at a 0.05 level of significance. The population consisted of 200,382 in-school adolescents across the state. A sample of 248 students from two secondary schools was selected for the study. The instrument used for data collection was a self-structured questionnaire known as the Mental Health Disorder Questionnaire (MHDQ). Data collected were analyzed using mean and standard deviation to answer the research questions, while Analysis of Covariance (ANCOVA) was used to test the null hypotheses. The findings revealed significant differences between the experimental and control groups on post-test measures. Specifically, the experimental subjects who received CBT showed a significant improvement in symptoms of Attention Deficit Hyperactivity Disorder (ADHD) and a marked decrease in examination phobia compared to the control group. Based on these findings, the study concluded that Cognitive Behavioural Therapy is an effective intervention for reducing mental health disorders among in-school adolescents in this context. Consequently, it was recommended that teachers and counsellors integrate CBT-based behavioural management strategies into classroom practices and that schools organize targeted workshops to help students manage examination anxiety.